Fabrication of 3-methoxyphenol sensor based on Fe3O4 decorated carbon nanotube nanocomposites for environmental safety: Real sample analyses - Rahman, Mohammed M.; Hussain, Mohammad Musarraf; Asiri, Abdullah M. (PLOS ONE, 2017)
Iron oxide ornamented carbon nanotube nanocomposites (Fe3O4.CNT NCs) were prepared by a wet-chemical process in basic means. The optical, morphological, and structural characterizations of Fe3O4.CNT NCs were performed using FTIR, UV/Vis., FESEM, TEM; XEDS, XPS, and XRD respectively. Flat GCE had been fabricated with a thin-layer of NCs using a coating binding agent. It was performed for the chemical sensor development by a dependable I-V technique. Among all interfering analytes, 3-methoxyphenol (3-MP) was selective towards the fabricated sensor. Increased electrochemical performances for example elevated sensitivity, linear dynamic range (LDR) and continuing steadiness towards selective 3-MP had been observed with chemical sensor. The calibration graph found linear (R2 = 0.9340) in a wide range of 3-MP concentration (90.0 pM 90.0 mM). The limit of detection and sensitivity were considered as 1.0 pM and 9×10−4 μAμM-1cm-2 respectively. The prepared of Fe3O4.CNT NCs by a wet-chemical progression is an interesting route for the development of hazardous phenolic sensor based on nanocomposite materials. It is also recommended that 3-MP sensor is exhibited a promising performances based on Fe3O4.CNT NCs by a facile I-V method for the significant applications of toxic chemicals for the safety of environmental and health-care fields.